Moderation, Pandemics and the Era of Disruption: Strengthening Religious Literacy in Urban Millennials after the Outbreak of Covid-19 - Yasin, Muhamad; Khasbulloh, M. Nabil (Didaktika Religia, 2022)
This study explores strategies to increase moderate religious literacy among urban millennials post-Covid-19 in the era of disruption. It focuses on the development of religious literacy skills and examines their contribution to the promotion of religious moderation. Using a phenomenological qualitative approach, data was collected through participant observation and independent interviews to ensure in-depth analysis. Data were processed through reduction, display, inference and verification, with validity tested through credibility, transferability, dependability and confirmability. The findings highlight that strengthening religious literacy involves equipping millennials with the ability to understand and engage with religious issues through skills such as reflection, inquiry, empathy, critical analysis, synthesis and communication. This promotes an understanding of Islam as a religion of peace, tolerance and inclusiveness. Key contributions to religious moderation include: fostering critical thinking and adaptability in interpreting religious content; enhancing the ability to identify diverse beliefs and practices; and fostering a preventive attitude towards hate speech disguised as religious rhetoric.